Heavy‐Atom‐Modulated Supramolecular Assembly Increases Antitumor Potency against Malignant Breast Tumors via Tunable Cooperativity. Issue 2 (3rd December 2020) - Guo, Zhengqing; He, Hui; Zhang, Yi; Rao, Jiaming; Yang, Tao; Li, Ting; Wang, Lu; Shi, Mengke; Wang, Mengya; Qiu, Shihong; Song, Xue; Ke, Hengte; et al.
Abstract: Triple‐negative breast cancer (TNBC) remains with highest incidence and mortality rates among females, and a critical bottleneck lies in rationally establishing potent therapeutics against TNBC. Here, the self‐assembled micellar nanoarchitecture of heavy‐atom‐modulated supramolecules with efficient cytoplasmic translocation and tunable photoconversion is shown, for potent suppression against primary, metastatic, and recurrent TNBC. Multi‐iodinated boron dipyrromethene micelles yield tunable photoconversion into singlet oxygen and a thermal effect, together with deep penetration and subsequent cytoplasmic translocation at the tumor. Tetra‐iodinated boron dipyrromethene micelles (4‐IBMs) particularly show a distinctly enhanced cooperativity of antitumor efficiency through considerable expressions of apoptotic proteins, potently suppressing subcutaneous, and orthotopic TNBC models, together with reduced oxygen dependence. Furthermore, 4‐IBMs yield preferable anti‐metastatic and anti‐recurrent efficacies through the inhibition of metastasis‐relevant proteins, distinct immunogenic cell death, and re‐education of M2 macrophages into tumoricidal M1 phenotype as compared to chemotherapy and surgical resection. These results offer insights into the cooperativity of supramolecular nanoarchitectures for potent phototherapy against TNBC. Abstract : Self‐assembled multi‐iodinated boron dipyrromethene micelles (IBMs), via the interplay of both π–π stacking and hydrophobic interactions, are reported. These IBMs cause efficient cascade delivery into cytoplasm and tunable photoconversion for yielding potent antitumor synergy against triple‐negative breast cancer together with distinctly reduced recurrence and metastasis through the reversal of tumor immunosuppression.